Drives and Control for Industrial Automation - Tan, Kok Kiong. (Advances in Industrial Control,, 2011)
Drives and Control for Industrial Automation presents the material necessary for an understanding of servo control in automation. Beginning with a macroscopic view of its subject, treating drives and control as parts of a single system, the book then pursues a detailed discussion of the major components of servo control: sensors, controllers and actuators. Throughout, the mechatronic approach – a synergistic integration of the components – is maintained, in keeping with contemporary practice. The authors’ holistic approach does not preclude the reader from learning in a step-by-step fashion – each chapter contains material that can be studied separately without compromising understanding. Drives are described in several chapters organized according to the way they are usually classified in industry, each comprised of its actuators and sensors. The controller is discussed alongside. Topics of recent and current interest – piezoelectricity, digital communications and future trends – are detailed in their own dedicated chapters. Drives and Control for Industrial Automation is primarily written for engineers and researchers interested in the applications of sensors, actuators and control systems in the automated environment. The discussion is thorough with the basics laid out succinctly but in sufficient detail to be useful to non-expert readers so students will also find this monograph a profitable source of information.